MONITORING LAMPU DAN PELACAK LOKASI MOBIL DENGAN FITUR KEAMANAN SWITCH CUT OFF ENGINE BERBASIS ARDUINO - Muktiyanto, Robby; Priyandoko , Gigih; Setiawidayat, Sabar (JASEE Journal of Application and Science on Electrical Engineering, 2024)
It's hard to know if one person does it. All this time, checking the rear lights is done conventionally by looking directly behind the car and requiring two people, such a way is less efficient. Besides, the car owner needs to know the location of the car, if the car is out of control of the owner. The research builds a light monitoring system and a car location tracker with a button to turn off the engine remotely using a smartphone. The research uses ACS712 sensors, Arduino Mega, Buzzer, LCD 16x2 with I2C modules, NodeMCU ESP8266, GPS module, WIFI modem, Relay module and the MIT APP Inventor Android app. This system's communication protocol uses the MQTT protocol, and the broker of this system uses the private broker's cloud. Researching the monitoring of lights using Panther and Genio cars, the system can distinguish when there are sensors that don't detect current, the buzzers are ringing and the LCD displays the "Lamp Off" character, as well as showing which lights are switched off. When all the sensors detect current then the buzzer is off, and the lcd displages the "OKE SYSTEM". The tracker system can display coordinate points and can be integrated with google maps. As well as the relay module can be controlled using buttons on the application so that the machine can die. This whole system uses smartphones remotely